Learning Japanese Passive Voice by Sri Lankan Learners - Preethi Dinusha Pinnaduwa (Universitas Negeri Semarang, 2022)
The purpose of this study is to examine the difficulties of learning Passive voice and to identify the type of errors learners do when producing Japanese passive sentences. It also aims to find strategies to minimize the errors in Passive sentences and reduce the difficulties in learning. The participants in this research are, learners of secondary schools and adult learners aged 20 to 40 in private institutes in three districts of Sri Lanka. A passive grammar test and a questionnaire have been used as the measuring instruments for this study. The grammar test was done by 100 learners while the questionnaire was answered by 94 learners. After the data was collected, a cross-sectional analysis was used to analyse the data. The results show that errors were done in the word order of the passive sentences, usage of the particles, construction of the passive verbs, using passive on transitive and intransitive verbs, and, construction of causative passive verbs. The researcher concludes, that to reduce the errors, strategies such as watching Japanese videos and dramas, making friends with Japanese nationals, gaining a good knowledge of the Japanese culture, memorizing, and making many passive sentences can be used. Keywords: Passive voice of Japanese; difficulties in learning; errors in Passive sentences; Secondary school learners and adult learners. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Passive VoiceJapanese Sri Lankan Learners